AL-USHÛL AL-‘ARABIYYAH LI ASMÂ AL-ISYÂRAH FÎ LUGHÂT AL-‘ÂLAM MIN MANZHÛR NAZHARIYYAH JADZR AL-KALIMAH - Zaidan Ali Jassem (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This paper aims to establish the Arabic cognates or origins of